In Type 2 Diabetic Patients Prevalence of Hepatitis C Virus Infection - Adeen Zahoor, Iram Shehzadi, Shaharyar Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Aims: To determine the prevalence of the hepatitis C virus in people with type 2 diabetes and to look for any links between the two Study Design: Descriptive studys Place and Duration: Rural Health Centre Vanike Tarar, Hafizabad. April 2021-Dec 2021 Methodology: A total of 120 people with type 2 diabetes were included in the study. Patient’s age ranged from 20 to 80 years. A specified Performa was used to record all of the relevant data. Complete data sets were analysed using SPSS 24.0. Results: There were 55% males and 45% female in the entire study. Out of 120 confirmed diabetic patients, 40 (33.3%) were seropositive for anti HCV antibodies while 80 (66.7%) were negative. The sero-prevalence of HCV in female was 21 (52.5%) while in male it was 19 (47.5%). Conclusion: Patients with Type 2 Diabetes mellitus are more likely to be infected with HCV, according to our research.